Report on Minor Irrigation Works in Assam State - Committee on Plan Projects Planning Commission (Planning Commission, Government of India, 1965)
The Report on Minor Irrigation Works in Assam evaluates the state of irrigation in a region characterized by abundant rainfall but irregular monsoon patterns, which limit consistent crop cultivation. The study identifies underutilized diversion canals, limited groundwater exploitation, and inadequate water management as key constraints. Recommendations focus on enhancing irrigation infrastructure, promoting crop diversification, establishing local irrigation cooperatives, implementing monitoring systems, and educating cultivators on efficient practices. The report emphasizes the potential for a second crop through improved irrigation and advocates for a legal framework to regulate irrigation projects. Effective implementation of these measures could significantly increase agricultural productivity, strengthen Assam’s contribution to national food security, and ensure sustainable water resource management.
Committee on Plan Projects (Irrigation Team) New Delhi September 1965
Keywords: Minor Irrigation; Assam; Groundwater; Tube Wells; Crop Productivity; Irrigation Management; Water Distribution; Drought Mitigation; Agricultural Development; Irrigation Planning